Folk dance (Columbus, Ohio Silver Burdett Ginn, 1995)
In this video, viewers learn about the community aspects of folk dance. A story about the creation of folk dance is told and patterns and formations in dances demonstrated.
Episode 1: The story -- episode 2: Folk dance (Colombia) -- episode 3: Line dance (Turkey) -- episode 4: Square dance (United States) -- episode 5: Circle dance (Russia) -- episode 6: La raspa (Mexico).
Series producers : Jane Beethoven, Rosanne Emery.
Host: Synia Carroll-McQuillan ; Puppeteer: Drew Allison.
Keywords: Folk dancing; Folk dancing -- Colombia; Line dancing -- Turkey; Square dancing -- United States; Folk dancing -- Russia; Folk dancing -- Mexico